CHARACTERISTICS OF TESTICULAR TORSION IN ARIFIN ACHMAD REGIONAL GENERAL HOSPITAL, PEKANBARU, RIAU PROVINCE, INDONESIA - Zamzami, Zuhirman; Yunfaista, Yenri (National Journal of Medical Research, 2018)
Background: Testicular torsion is an abnormality disease in the testicle because torsion of the spermatic cord resulting in occlusion and strangulation vascularization of the veins and arteries to the testes and epididymis. This study aimed at describing the characteristics of testicular torsion of urology patients based on age, clinical symptom, physical examination, supporting examination, duration and treatment. Materials and methods: We reviewed medical records of urology patients testicular torsion in Arifin Achmad Regional General Hospital, Pekanbaru, Riau Province, Indonesia in 2011 - 2016. Statistical analysis of univariate was used. Approval on the study was obtained from the Ethical Review Board for Medicine and Health Research, Medical Faculty, University of Riau. Results: There were 6 patients in this study in which testicular torsion was in 11-20 year old age group in 50% patients. The most frequent clinical symptom was scrotal pain in 83.3%. The physical examination of cremaster reflex was absent in 100% patients. The most frequent supporting examination was conventional scrotal ultrasonography in 66.6% patients. The duration of testicular torsion in > 12 hour was in 83.3%. The most frequent management was orchidectomy in 83.3% patients. Conclusion : Testicular torsion in our hospital was characterized by mostly in young age, clinical symptom was scrotal pain, Cremaster reflex was negative in 100% in physical examination, supporting examination was conventional scrotal ultrasonography, duration symptom was in > 12 hours and managed by orchidectomy.